Bücklund transformation for spacelike curves in the Minkowski space-time - OZDEMIR, M.; ERDOGDU, M.; SIMSEK, H.; AZIZ ERGIN, A. (Kuwait Journal of Science, 2014)
The main purpose of this paper is to construct a Bücklund transformation between two spacelike curves with the same constant curvature in Minkowski space-time by considering some assumptions. Moreover, we give the relations between curvatures of these two spacelike Bücklund curves.